Європейський досвід урегулювання криз: на матеріалі конфлікту в Боснії і Герцеговині (1991-1995 рр.) - Руда, В. (Схід, 2010)
У статті розглядаються питання врегулювання одного з найбільш гострих конфліктів на Балканах - конфлікту в Боснії і Герцеговині - і роль Європейського Союзу в цьому процесі. Показано еволюцію позиції ЄС під час боснійської кризи: від прагнення будь-яким способом зберегти єдність СФРЮ, до сприяння утворенню окремих держав. The article is devoted to the problem of regulation of one the most acute conflicts on the Balkans, i.e. conflict in Bosnia and Herzegovyna. It gives special attention to the role of European Union in this process. The article shows the change of the EU positions in times of the Bosnian crisis, from wish to preserve the unity of the SFRY at all costs, to encouraging the creation of two separate states.